Statute Meets Custom: Explaining Provincial Variation in Child Marriage After Indonesia’s 2019 Reform - Yudisthira, I Made; Setyonaluri, Diahhadi (Jurnal Ekonomi Kependudukan dan Keluarga, 2026)
This study investigates whether Indonesia’s 2019 Marriage Law reform, which raised the minimum legal age of marriage to 19, has been associated with lower child marriage prevalence. Using province-level aggregates from the 2022 Indonesian National Socio-Economic Survey (SUSENAS, N = 1,237,946), we distinguish documented and undocumented unions and estimate Ordinary Least Squares models with controls for poverty, education, assets, rural residence, religious composition, and marriage dispensations. Descriptive maps show prevalence is highest in South Kalimantan (18%), East Java (17%), and West Java (17%), with undocumented unions concentrated in West Nusa Tenggara (7%), Banten (5%), Papua (5%), and West Sulawesi (5%). Regression results indicate that provinces with a larger share of adolescents aged 16–19 in 2019—the cohort directly exposed to the reform—exhibit higher child marriage prevalence, with a coefficient of 4.626 (p This study investigates whether Indonesia’s 2019 Marriage Law reform, which raised the minimum legal age of marriage to 19, has been associated with lower child marriage prevalence. Using province-level aggregates from the 2022 Indonesian National Socio-Economic Survey (SUSENAS, ), we distinguish documented and undocumented unions and estimate ordinary least squares models by controlling for poverty, education, assets, rural residence, religious composition, and marriage dispensations. Descriptive maps show child marriage prevalence is highest in South Kalimantan (18%), East Java (17%), and West Java (17%), with undocumented unions concentrated in West Nusa Tenggara (7%), Banten (5%), Papua (5%), and West Sulawesi (5%). Regression results indicate that provinces with a larger share of adolescents aged 16–19 in 2019—the cohort directly exposed to the reform—exhibit higher child marriage prevalence, with a coefficient of 4.626 (p